Peran dimensi orientasi kewirausahaan dan kapabilitas pemasaran pada kinerja usaha skala kecil dan menengah - Fifi Efendi; Perengki Susanto (Universitas Negeri Padang, 2021)
The aim of this study is to look into (1) the impact of innovation on SMEs' performance; (2) the consequence of risk-taking on SMEs' performance; (3) the effect of proactiveness on SMEs' performance; (4) the influence of competitive aggressiveness on SMEs' performance; (5) the effect of autonomy on SMEs' performance; and (6) the impact of marketing capabilities on SMEs' performance. This is a survey-based quantitative study. The managers or owners of SMEs in Padang City as a population of this study. The research sample employs a non-probability sampling method, in which the sample is chosen based on a set of criteria. Sample size up to 150 samples were taken. PLS-SEM analysis was used to analyze the empirical data in the study. According to findings, risk-taking, autonomy, and marketing capabilities all had a positive and significant impact on the performance of SMEs. However, innovativeness, proactiveness, and competitive aggressiveness have no influence on performance of SMEs. The implication will be discussed later.